2016
DOI: 10.1136/bjophthalmol-2015-306902
|View full text |Cite
|
Sign up to set email alerts
|

Scleritis associated with relapsing polychondritis

Abstract: Scleritis may be the first manifestation whose study leads to the diagnosis of RP. Scleritis associated with RP is more often bilateral, necrotising, recurrent and associated with decrease of vision than scleritis associated with other SIMD. About 69.2% of patients will have an additional SIMD disorder. Scleritis associated with RP most often will require immunomodulatory therapy. Occasionally, scleritis with RP may appear while using antitumor necrosis factor α agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Scleritis may be the initial manifestation of RP and has some typical characteristics when connected with RP. Sainz-de-la-Maza et al [22], in a retrospective analysis of 13 RP patients diagnosed with scleritis, compared 113 patients with other autoimmune diseases and showed that scleritis in RP patients was more often bilateral ( p = 0.001), necrotising (23.1%; p = 0.02), recurrent ( p = 0.001), and associated with decreased vision ( p = 0.012). A significant proportion of RP patients from that study (9/13, 69.2%) had one or more other autoimmune conditions, which on average preceded RP by nine years (between two and 21 years).…”
Section: Discussionmentioning
confidence: 99%
“…Scleritis may be the initial manifestation of RP and has some typical characteristics when connected with RP. Sainz-de-la-Maza et al [22], in a retrospective analysis of 13 RP patients diagnosed with scleritis, compared 113 patients with other autoimmune diseases and showed that scleritis in RP patients was more often bilateral ( p = 0.001), necrotising (23.1%; p = 0.02), recurrent ( p = 0.001), and associated with decreased vision ( p = 0.012). A significant proportion of RP patients from that study (9/13, 69.2%) had one or more other autoimmune conditions, which on average preceded RP by nine years (between two and 21 years).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they allowed a GC-sparing effect and were associated with a good safety profile [ 11 ]. Successful results with TNFα inhibitors have also been reported in three patients affected by relapsing polychondritis (RP) [ 20 ]. Table 1 shows the retrieved studies regarding TNF inhibitors employed in the management of non-infectious scleritis and some of their respective findings.…”
Section: Tumor Necrosis Factor Inhibitorsmentioning
confidence: 99%
“…Scleritis/episcleritis is the most common ocular complication associated with RPC (Table 3) [10,[26][27][28][29][30][31][32][33][34]. Most cases of scleritis occur bilaterally.…”
Section: Scleramentioning
confidence: 99%
“…Most cases of scleritis occur bilaterally. Several case series revealed that diffuse anterior scleritis was the most common (Figure 1), but nodular (Figure 2A) or necrotizing anterior scleritis and posterior scleritis (Figure 2B) were also observed (Table 4) [32][33][34][35]. Sainz-de-la-Maza et al compared patients with scleritis associated with RPC and other systemic immune-mediated diseases and showed that it is more often bilateral, recurrent, necrotizing, and associated with visual disturbance than scleritis associated with other systemic immune-mediated diseases [32].…”
Section: Scleramentioning
confidence: 99%